Legal Regulation of Relations in the Field of Exhibition and Fair Activities - A. M. Alikieva; O. P. Elantseva (Сибирское юридическое обозрение, 2020)
Legal regulation of the organization of exhibition, fair and congress activities has long been characterized in Russian legislation by a certain gap. The current legislation does not contain the necessary rules and administrative procedures that can solve some problematic issues that arise during the organization and holding of fairs in the settlements. The development of this segment of the service sector is relevant both for authorities and for foreign partners, investors, legal entities and individuals. Participants of exhibition and fair events are interested in simplifying the administrative procedures for organizing and conducting fairs and the participation of citizens and legal entities in them. Based on a study of regulatory legal acts, law enforcement practice of the constituent entities of the Russian Federation and local self-government bodies, the Authors made suggestions for improving legal regulation and law enforcement in this area of legal relations.